2015
DOI: 10.5365/wpsar.2015.6.2.hyn_012
|View full text |Cite
|
Sign up to set email alerts
|

Medicines management in the Philippines public sector during the response to Haiyan

Abstract: While the process of managing medicines during disasters did not differ greatly from non-emergency situations, the Haiyan experience highlighted the system's weaknesses. With the current gaps in implementation, as well as the logistical obstacles brought about by disasters, there is a need to have integrated mechanisms for medicines management in the Philippines. This assessment provided an important opportunity to review the medicines management policies at national and local levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…This can be associated with the lack of clear guidelines/ criteria being followed on accepting donations at the local level. This finding is similar to what was found in the study of supply chain practices of rural communities affected by typhoon in the Philippines where donated pharmaceuticals occupied a lot of space in the storage areas and caused an additional burden to dispose unwanted products 3 . The process of managing medicines during disasters is not greatly different than the usual practice; however, the response to typhoon Haiyan highlighted the system' s weaknesses.…”
Section: Municipal Medicines Supply Chain Managementsupporting
confidence: 89%
See 2 more Smart Citations
“…This can be associated with the lack of clear guidelines/ criteria being followed on accepting donations at the local level. This finding is similar to what was found in the study of supply chain practices of rural communities affected by typhoon in the Philippines where donated pharmaceuticals occupied a lot of space in the storage areas and caused an additional burden to dispose unwanted products 3 . The process of managing medicines during disasters is not greatly different than the usual practice; however, the response to typhoon Haiyan highlighted the system' s weaknesses.…”
Section: Municipal Medicines Supply Chain Managementsupporting
confidence: 89%
“…Thus, LGUs had difficulty in generating reports. This is coherent with Salenga et al (2015) 3 study on the medicines supplies system of selected typhoon-affected areas in the Philippines, which indicates that…”
Section: Municipal Medicines Supply Chain Managementsupporting
confidence: 81%
See 1 more Smart Citation
“…This equates to a fair achievement of health standards, which also underscored the need to revisit programs and policies aligned with the prices, availability and affordability of essential medical products, vaccines, and technologies in the province. In the local context, public hospitals are responsible for ensuring the availability of essential medicines in their health facilities (Salenga, et al, 2015). However, because of budgetary constraints or inefficiencies in supply chain management, the supplies of medicines in the public health facilities become unreliable.…”
Section: Status Of Health System and Level Ofmentioning
confidence: 99%
“…24 Medicine management during the response was difficult and was compounded by receiving donation of short-dated, near-expiry and unnecessary items which created additional burden on the health system. 25 A small study of self-reported health costs suggested many people had catastrophic out-of-pocket health expenditures with consultation and transportation costs as the main barriers to health service utilization.…”
mentioning
confidence: 99%